PENGGUNAAN MODEL PEMBELAJARAN WORD SQUARE UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PELAJARAN PENDIDIKAN KEWARGANEGARAAN DI KELAS V SD NEGERI 054938 KAB. LANGKAT - Nurmayani Nurmayani (PGSD Universitas Negeri Medan, 2018)
This study aims to determine the improvement of student learning outcomes by using the model of learning Word Square padapelajaran civic education in VSD class 054938 academic year 2017 / 2018. The problem in this study is the result of student's civic education learning is low on the material freedom of organization in class V SD Negeri 054938 Pangkalan Dress up academic year 2017/2018. This type of research is classroom action research conducted with 2 cycles and 4 stages namely, planning, implementation, observation, and reflection. With the subjects of research are 24 students of grade V SD Negeri 054938 with rician 12 men and 12 women. The data collection tool is a test of learning outcomes and observation sheets. Keywords: Word Square, Student Learning Outcomes, Citizenship Education.